2011
DOI: 10.5301/ejo.2011.8359
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Objective Vault and Effect on Vision Outcomes after Implantable Collamer Lens Implantation: 1-Year Follow-up

Abstract: Implantable Collamer lens vault over the crystalline lens had the tendency toward a slight decrease with time and did not significantly affect the vision outcome 1 year after surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(18 citation statements)
references
References 18 publications
2
16
0
Order By: Relevance
“…Previous studies [4, 5, 1719, 23] investigating vault following ICL implantation have demonstrated a tendency for the vault to decrease slightly in the long term for both conventional ICLs and hole ICLs. Currently, there is limited literature available investigating changes in vault as early as 1 day following implantation of ICL V4c IOLs.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Previous studies [4, 5, 1719, 23] investigating vault following ICL implantation have demonstrated a tendency for the vault to decrease slightly in the long term for both conventional ICLs and hole ICLs. Currently, there is limited literature available investigating changes in vault as early as 1 day following implantation of ICL V4c IOLs.…”
Section: Discussionmentioning
confidence: 98%
“…We found that the change in pupil size was a critical factor to the vault change, and postoperative vault was associated with preoperative ACD, WTW, horizontal and vertical STS in eyes implanted with ICL V4 and ICL V4c. In recent studies, rotating Scheimpflug imaging (Pentacam) [1719], anterior segment OCT [4, 13, 20, 21], and UBM [22] have been used to measure the phakic IOL vault and have all provided accurate and reproducible measures of anterior segment biometry. In our present study, we used the rotating Scheimpflug imaging system (Pentacam) that has proved to be a repeatable measurement to evaluate the vault [17].…”
Section: Discussionmentioning
confidence: 99%
“…The studies reporting vault based on WTW and ACD measurements generally employed the manufacturer’s sizing nomogram and reported data on a total of 2,263 eyes. The authors’ methods state, for example, that “size was determined based on the horizontal WTW distance and ACD, measured with the Orbscan II device following the manufacturer’s recommendations” 13 or “The ICL diameter was individually determined based on the horizontal WTW distance and ACD measured with Orbscan II (Bausch & Lomb, Rochester, NY) following the manufacturer’s recommendations” 35 or “The size of ICL was also chosen by the manufacturer based on the horizontal corneal diameter and ACD” 36 or “The size of the ICL was also chosen by the manufacturer on the basis of the horizontal corneal diameter and the ACD measured by scanning-slit topography (Orbscan IIz)”. 11 …”
Section: Reported Sizing Methodologiesmentioning
confidence: 99%
“…As we know, the ideal phakic IOL position show the optical zone located on the center of the pupil, and both haptics on the sulcus with an appropriate vault (250 μm -750 μm). Because excessive (> 750 μm) or insufficient (< 250 μm) vault lead to complications such as pigmentary loss, glaucoma or cataract, and the stability of vault becomes the major concern after ICL implantation [ 13 ]. The ICL dislocation usually results in an inappropriate vault [ 14 ].…”
Section: Introductionmentioning
confidence: 99%